Peran Modal Sosial, Kereligian, dan Perilaku Moral dalam Membentuk Kinerja Usaha Mikro dan Kecil dengan Aspek Demografi Sebagai Variabel Pengendali - Ani Murwani Muhar; Teguh Setiawan (Jurnal Dinamika Akuntansi dan Bisnis, 2015)
This study was motivated by the presence of non-financial aspects such as morality, religious, and the forms of social capital that can be applied as the important things in the increased competitiveness within the MSE. Increased competitiveness and encouraging impact on promoted business performance. Business performance can be viewed from two perspectives, namely the success of the business and entrepreneur performance. To that end, the study aims to describe: (1) The dimensions of social capital are associated with moral behavior, (2) frequency of participation rate religious that produce social capital level, (3) Effect of religious and capital dimensions social to moral behavior by demographics (gender, age) as a control variable, and (4) the effect of religious, social capital dimensions, and moral behavior on performance of SMEs. The research population was the MSEs in some industries who live in Medan city. They were food and beverage industry, the fashion industry, textile industry and textile products, handicrafts and goods from the industrial arts, industrial furniture, as well as pottery and decorative ceramics industry. Sampling technique in this study was conducted in 2 phases (two stage sampling). The gathering data in this study used field survey techniques directly by visiting the respondent. Based on calculated statistically showed that there was a significant relationship between the social capital dimensions and moral behavior. The entries of religious variables into the influence of social capital on moral behavior that controlled by the demographic factors, showed that only confidence and share your view variables have no relation to moral behavior. Related on the successful and business performance aspects, the empathy variable was a variable that perceived by SMEs actors can increase their business success and their business performance.This study was motivated by the presence of non-financial aspects such as morality, religious, and the forms of social capital that can be applied as the important things in the increased competitiveness within the MSE. Increased competitiveness and encouraging impact on promoted business performance. Business performance can be viewed from two perspectives, namely the success of the business and entrepreneur performance. To that end, the study aims to describe: (1) The dimensions of social capital are associated with moral behavior, (2) frequency of participation rate religious that produce social capital level, (3) Effect of religious and capital dimensions social to moral behavior by demographics (gender, age) as a control variable, and (4) the effect of religious, social capital dimensions, and moral behavior on performance of SMEs. The research population was the MSEs in some industries who live in Medan city. They were food and beverage industry, the fashion industry, textile industry and textile products, handicrafts and goods from the industrial arts, industrial furniture, as well as pottery and decorative ceramics industry. Sampling technique in this study was conducted in 2 phases (two stage sampling). The gathering data in this study used field survey techniques directly by visiting the respondent. Based on calculated statistically showed that there was a significant relationship between the social capital dimensions and moral behavior. The entries of religious variables into the influence of social capital on moral behavior that controlled by the demographic factors, showed that only confidence and share your view variables have no relation to moral behavior. Related on the successful and business performance aspects, the empathy variable was a variable that perceived by SMEs actors can increase their business success and their business performance.